The Influence of Instagram Social Media Promotion on Domestic Tourists' Decision to Visit Pandawa Beach Tourist Attraction - Wati, Ni Kadek Erma Anggara; Wayan Mertha, I; Kristiono Liestiandre, Hanugerah (Journal of Comprehensive Science, 2024)
At Present, Instagram significantly influences someone's interest in traveling to a place or tourist attraction. For example, many things can influence someone or tourists to visit, such as interesting content created by the managers of a tourist attraction. Currently, many tourist attraction accounts promote their tourism products through content on Instagram, such as videos or photos showcasing their products. There are also many Bali Tourism Instagram accounts that are popular among Indonesian tourists, especially millennials, making it easier for tourists to visit One of the attractions in Bali, the aim of this study is to identify the Influence of Social Media Promotion on Instagram Towards the Decision of Domestic Tourists to Visit Pandawa Beach Tourist Attraction.